2018
DOI: 10.4081/gc.2018.7853
|View full text |Cite
|
Sign up to set email alerts
|

Chances and challenges of comprehensive geriatric assessment training for healthcare providers

Abstract: Geriatrics is the medical specialty that deals with physical, psychological, social and functional aspects of the older adult and represents a most authentic form of personalized medicine. As such, it is successfully performed through its cornerstone instrument, the comprehensive geriatric assessment (CGA), which consistently shows its significant benefits since over 30 years. However, the high speed at which the world population ages and gets affected by chronic conditions, multimorbidity and functional impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Certainly, the proof of such an effect would require a special study design. Nevertheless, an assessor training in frailty measurement seems to be reasonable with future development of appropriate, more structured instruction and schooling systems in the CGA field [12]. Given an optimum low assessment time of 10 min (median) under our conditions (cohort 3), the MPI positions even more favorable in the ranking position of CGA tools with regard to time expenditure.…”
Section: Discussionmentioning
confidence: 89%
“…Certainly, the proof of such an effect would require a special study design. Nevertheless, an assessor training in frailty measurement seems to be reasonable with future development of appropriate, more structured instruction and schooling systems in the CGA field [12]. Given an optimum low assessment time of 10 min (median) under our conditions (cohort 3), the MPI positions even more favorable in the ranking position of CGA tools with regard to time expenditure.…”
Section: Discussionmentioning
confidence: 89%
“…Besides professional standards and ethics, a strong attitude towards patient relations, inter-professional team working, redefinition of roles and relations and/or communication build the ground for an integrated management and organization flow when offering CGA to older people and patients. Understanding how to best equip todays health and social care staff with these core competencies remains a challenge up to this point [48]. Some of the studies included indicated a variability in results according to profession [32,36].…”
Section: (4) Discussionmentioning
confidence: 99%
“…Furthermore, CGA can be applied across different care settings (e.g., primary care, hospital, local health and social care facilities), with different types of pathways and levels of intensity. Unfortunately, there are some barriers to the implementation of CGA, such as: 1) an inadequate definition of the characteristics of patients who could benefit the most from a multidimensional care pathway [ 1 ]; 2) a high heterogeneity of operational definitions of CGA [ 7 ]; 3) a lack specific training on CGA for social and healthcare staff involved in caring for older people [ 8 ]; 4) a poor definition of the professional skills required in the interdisciplinary team for drafting, implementing and monitoring CGA-based treatment plans. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%